“Next top” mouse models advancing CTCL research - Luo, Yixin; de Gruijl, Frank R.; Vermeer, Maarten H.; Tensen, Cornelis P. (Frontiers in Cell and Developmental Biology, 2024)
This review systematically describes the application of in vivo mouse models in studying cutaneous T-cell lymphoma (CTCL), a complex hematological neoplasm. It highlights the diverse research approaches essential for understanding CTCL's intricate pathogenesis and evaluating potential treatments. The review categorizes various mouse models, including xenograft, syngeneic transplantation, and genetically engineered mouse models (GEMMs), emphasizing their contributions to understanding tumor-host interactions, gene functions, and studies on drug efficacy in CTCL. It acknowledges the limitations of these models, particularly in fully replicating human immune responses and early stages of CTCL. The review also highlights novel developments focusing on the potential of skin-targeted GEMMs in studying natural skin lymphoma progression and interactions with the immune system from onset. In conclusion, a balanced understanding of these models' strengths and weaknesses are essential for accelerating the deciphering of CTCL pathogenesis and developing treatment methods. The GEMMs engineered to target specifically skin-homing CD4+ T cells can be the next top mouse models that pave the way for exploring the effects of CTCL-related genes.